Melatonin as an anti-inflammatory hormone bridging migraine relief and cancer immunity enhancement: a literature review - Zhu, Qian; Yang, Jin; Zhang, Jieying; Song, Qian; Zhang, XinXin; Li, Menghan; Zhang, Menglong; Shi, Lei; Song, Xiaoli (Frontiers in Immunology, 2025)
Melatonin, once relegated to the circadian periphery, has resurfaced as a pleiotropic immunomodulator capable of quelling neurogenic inflammation while invigorating antitumour defence. Migraine—and its disabling, episodic neurovascular pain—shares an “inflammatory genome”, defined here as a conserved danger-response gene set (NF-κB, NLRP3, IL1B, NOS2), with the metabolic chaos that subdues cytotoxic immunity in solid cancers; both ignite NF-κB, NLRP3 and reactive-oxygen cascades that erode tissue homeostasis. Emerging evidence shows that endogenous melatonin declines precede migraine attacks, and nightly supplementation rivals first-line preventives in shrinking monthly headache burden while restoring sleep architecture. In parallel, supraphysiological pulses re-programme tumour-associated macrophages toward an iNOS-rich M1 phenotype, amplify granzyme-B output from CD8+ T cells and down-tune PD-L1 expression on malignant and myeloid cells, thereby widening the therapeutic window of immune-checkpoint blockade. The same cytokines suffused during a migraine flare—IL-6, TNF-α, ROS—subvert antitumour surveillance; melatonin extinguishes these mediators, synchronises clock-gene–driven metabolism and stitches a biochemical thread between headache relief and cancer immunity. Nanocarrier formulations, chronobiology-guided dosing and rational combinations with CGRP inhibitors or PD-(L)1 antibodies are already advancing through translational pipelines. This review distils molecular pharmacology, pre-clinical models and early-phase trials to portray melatonin as a single, evolutionarily conserved molecule that orchestrates bilateral protection across nervous and oncologic frontiers. By integrating chronotherapy, immunology and neurovascular biology, we aim to identify diagnostic blind spots, repurpose therapeutics and chart a roadmap toward precision strategies that simultaneously alleviate migraine disability and fortify antitumour immunity.